The growing salience of moderate Islam - Mohamed Bin Ali (2024)
In steering his country towards an economy more broadly based on foreign direct investments and less reliant on oil, Crown Prince Mohammad Bin Salman has transformed the austere Wahhabi form of Islam in Saudi Arabia into a more moderate transnational variety. Other countries in the Middle East and Southeast Asia have similarly embarked on projects to moderate their versions of Islam, all of which, as in the Saudi case, add to their soft power.